Consumption of mixed spices and herbs and general well-being observed in case controlled Type 2 Diabetes Mellitus (T2DM) - Mahood, Tahir; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Zulkifli, Hidayatul Hafidzah; Azam, Siti Amirah (IACSIT Press, Singapore, 2014)
Herbs and spices are believed to possess hypoglycemic effects in Type 2 Diabetes Mellitus (T2DM) patients. 20 patients were recruited from the Medical Outpatient Department of Hospital Tengku Ampuan Afzan (HTAA) Kuantan Pahang, Malaysia. Informed consent was obtained and the study protocol was approved by the International Islamic University Malaysia Research Ethical Committee (IREC) & Clinical Research Committee (CRC) Ministry of Health Malaysia. 10 patients were provided with placebo while the other 10 patients received 4 gram of mixed herbs and spices. The total duration of the trial was 30 days. Blood samples were collected before and at the end of the feeding period, which were analyzed for parameters namely fasting blood sugar (FBS), 2 hours post prandial blood sugar (2HPP), glycosylated haemoglobin (HbA1c) and lipid (profile) concentrations. The results showed a significant reduction (p<0.05) in the FBS and HbA1c; however no changes were seen in the other parameters. The present study indicates that the mixed herbs & spices have beneficial effects in the control of T2DM as well as the general wellbeing of the patients, as during the feeding period, the patients felt more energetic.